Effective intensity distributions used for direct laser interference exposure. Issue 68 (25th July 2015) - Xu, Jia; Wang, Zuobin; Zhang, Ziang; Wang, Dapeng; Weng, Zhankun
<x xml:space="preserve">Abstract</x> Effective intensity distributions are used for direct multi-beam interference by controlling the exposure beam intensities.